Growth of the human corpus callosum: modular and laminar morphogenetic zones - Jovanov-Milosevic, Natasa; Culjat, Marko; Kostovic, Ivica (Frontiers in Neuroanatomy, 2009)
The purpose of this focused review is to present and discuss recent data on the changing organization of cerebral midline structures that support the growth and development of the largest commissure in humans, the corpus callosum. We will put an emphasis on the callosal growth during the period between 20 – 45 postconceptual weeks (PCW) and focus on the advantages of a correlated histological/magnetic resonance imaging (MRI) approach. The midline structures that mediate development of the corpus callosum in rodents, also mediate its early growth in humans. However, later phases of callosal growth in humans show additional medial transient structures: grooves made up of callosal septa and the subcallosal zone. These modular (septa) and laminar (subcallosal zone) structures enable the growth of axons along the ventral callosal tier after 18 PCW, during the rapid increase in size of the callosal midsagittal cross-section area. Glial fibrillary acidic protein positive cells, neurons, guidance molecule semaphorin3A in cells and extracellular matrix (ECM), and chondroitin sulfate proteoglycan in the ECM have been identified along the ventral callosal tier in the protruding septa and subcallosal zone. Postmortem MRI at 3 Tesla can demonstrate transient structures based on higher water content in ECM, and give us the possibility to follow the growth of the corpus callosum in vivo, due to the characteristic MR signal. Knowledge about structural properties of midline morphogenetic structures may facilitate analysis of the development of interhemispheric connections in the normal and abnormal fetal human brain.